Analisis Volume Lalu Lintas Pada Simpang Bersinyal Studi Kasus Persimpangan Jl. Rajawali – Jl. Hiu Putih Di Kota Palangka Raya - Purnama Sari, Elsa Purnama Sari; Robby; Murniati (Jurnal Basement : Jurnal Teknik Sipil, 2023)
Crossroads are nodes in the road network where road segments meet and vehicle traffic trajectories intersect. At the intersection of Jl. Rajawali  – Jl. Hiu Putih, traffic flow during peak hours will increase so it needs to be handled. The purpose of this study was to determine the traffic volume at the signalized intersection at Jl. Rajawali  – Jl. Hiu Putih which will later be useful as information needed for the planning, design, management and operation phases of the road. The research method used is a direct survey in the field to obtain primary data in the form of road geometry, environmental conditions, and traffic volume. Secondary data is in the form of a map of field conditions around the intersection, and population data. Data collection was carried out for one week from Monday 05 September 2022 to Sunday 11 September 2022. The data taken was in the form of road width and the amount of traffic flow at each intersection. The research results obtained are the highest traffic volume at the intersection of four Jl. Rajawali  – Jl. Hiu Putih is on Friday (north) approach of 256 lvu/hour, on Sunday (east) approach of 238 lvu/hour, on Monday (south) approach of 299 lvu/hour and on Thursday (west) approach of 142 lvu/hour. This data is used as an analysis to determine traffic volume. Data were analyzed using the Indonesian Road Capacity Guidelines (PKJI) 2014.